2010
DOI: 10.1371/journal.pone.0014270
|View full text |Cite|
|
Sign up to set email alerts
|

Immune Protection Induced on Day 10 Following Administration of the 2009 A/H1N1 Pandemic Influenza Vaccine

Abstract: BackgroundThe 2009 swine-origin influenza virus (S-OIV) H1N1 pandemic has caused more than 18,000 deaths worldwide. Vaccines against the 2009 A/H1N1 influenza virus are useful for preventing infection and controlling the pandemic. The kinetics of the immune response following vaccination with the 2009 A/H1N1 influenza vaccine need further investigation.Methodology/Principal Findings58 volunteers were vaccinated with a 2009 A/H1N1 pandemic influenza monovalent split-virus vaccine (15 µg, single-dose). The sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(19 reference statements)
0
12
0
1
Order By: Relevance
“…Fourteen studies were single-arm (with respect to pandemic vaccines) or non-randomized trials and were thus included in proportion meta-analyses only [9], [13], [14], [16], [21], [22], [27], [31], [32], [34], [55], [57], [58]. One of the above papers also reported data on a randomized clinical trial (RCT) [55], as did the remaining 19 papers, which reported the results of another 21 RCTs [8], [11], [12], [15], [17], [18], [19], [23], [24], [25], [26], [28], [29], [30], [33], [35], [37], [39], [54], [59], for a total of 22 RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were single-arm (with respect to pandemic vaccines) or non-randomized trials and were thus included in proportion meta-analyses only [9], [13], [14], [16], [21], [22], [27], [31], [32], [34], [55], [57], [58]. One of the above papers also reported data on a randomized clinical trial (RCT) [55], as did the remaining 19 papers, which reported the results of another 21 RCTs [8], [11], [12], [15], [17], [18], [19], [23], [24], [25], [26], [28], [29], [30], [33], [35], [37], [39], [54], [59], for a total of 22 RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…One of the key functions of an- or more are associated with protection from influenza virus infection and are often used as markers of successful immunization in influenza vaccine trials (23,30). During the first few days of an infection, the neutralizing antibody titers are often low (34). However, the magnitude of nonneutralizing antibodies during this period has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent report [24] revealed that a neutralizing antibody to protect against H1N1 pdm09 infection increased as early as 10 days after vaccination against H1N1 pdm09. In addition, a stronger response to increase the neutralizing antibody to H1N1 pdm09 was observed in individuals with an elevated preexisting seasonal influenza antibody.…”
Section: Discussionmentioning
confidence: 97%